Electoral competition and policy-making under the fourth Merkel government: driven by ‘Fridays for future’ and the pandemic? - Zohlnhöfer, Reimut; Engler, Fabian (German politics, 2024)
Did electoral competition shape the policies of the fourth Merkel government? We answer this question in five steps. First, we theoretically discuss under which conditions electoral competition affects public policies. Only in publicly salient issue areas in which opposition parties advocate credible alternatives and only if policy satisfaction influences voting intention will the government modify its policies. Next, we identify the two most salient issue areas, climate change and the Corona pandemic. Third, opposition parties offered credible alternatives, the Greens (and the Left) in climate policy and the FDP (and the AfD) regarding Corona management. Fourth, governing parties could not be certain to participate in the next government. Furthermore, voting intention for the Christian democrats as leading party of the government was related to policy success, while the Greens (and the Left) and the FDP (and the AfD) could benefit from dissatisfaction with climate change policy and Corona management, respectively. Finally, only regarding climate change did the government respond to electoral pressure by an increase in press releases, while communication about Corona was driven by voters’ problem perception. These findings are corroborated by brief case studies of policy-making processes.
Gesehen am 01.08.2024